Statistique appliquée aux images NOAA pour le suivi du couvert végétal des bassins versants d'Aghien et de la Mé - Zamblé Armand Tra Bi; Djibril Noufé; Bamory Kamagaté; Kôkôh Rose Effebi; Yemou Jeanne N’tain; Seydou Diallo; Fabrice Nguetta; Karoui Hela; Droh Laciné Goné; Jean Louis; Luc Séguis (VertigO)
A pioneering area of Ivorian cocoa and coffee plantation agriculture, the watersheds of Aghien and Mé were quickly subjected to intense deforestation. The phytogeographic landscape has been constantly changing since the country's independence in 1960. These landscape changes are linked to the pecuniary interests of different perennial crops over the years (coffee, cocoa, rubber, palm oil and sweet banana). The study of the evolution of the vegetation cover of the watersheds of Aghien and Mé from 1982 to 2013 aims to take stock of the spatio-temporal transformations of the landscape units of these two basins. To carry out this study, were used jointly remote sensing, statistical tests of trend and rupture and field surveys. Daily images of index of vegetation NDVI (Normalized Difference Vegetation Index) of NOAA (National Oceanic and atmospheric administration) were compiled. Thus, descriptive statistical analyzes and stationarity tests were carried out on the basis of the pixel values of these images. The results of these tests produced in the cartographic form have been investigated in the field. The results of the study indicate, at the temporal level, a major break between 1993 and 1997. In addition, three levels of spatial discrimination are clearly distinguishable : the increasingly urbanized area of the Aghien basin ; the northeast of the Mé basin, area of high production of perennial crops (cocoa, hevea, coffee, oil palm, etc.) and the rest of the basin characterized by a mosaic food crop-export crop.